A global integral terminal sliding mode control based on a novel reaching law for a proton exchange membrane fuel cell system. (1st November 2021) - Napole, Cristian; Derbeli, Mohamed; Barambones, Oscar
Abstract: Proton exchange membrane fuel cells are devices with huge potential for renewable and clean industries due to their high efficiency and low emissions. Since the proton exchange membrane fuel cell employed in this research supplied a low output voltage, it was encouraged to use a boost converter with a designed non-linear controller to provide a suitable end-user voltage. In this paper, we proposed a novel control framework based on sliding mode control, which is a global integral sliding mode control linked with a quick reaching law that has been implemented in a commercial fuel cell system Heliocentris FC50 through a dSpace 1102 control board. We compared the strategy with a conventional sliding mode controller and an integral terminal sliding mode controller where we addressed a Lyapunov stability proof has for each structure. We contrasted the experimental outcomes where we proved the superiority of the proposed novel design in terms of robustness, convergence speed. Additionally, as the sliding mode controllers are well known by the energy consumption caused by the chattering effect, we analysed every framework in these terms. Finally, it was found that the proposed structure offered an enhancement in the energy consumption issues. Moreover, the applicability of the proposed control scheme has been demonstrated through the real time implementation over a commercial fuel cell. Graphical abstract: Highlights: A novel control strategy is established for a fuel cell power system. Two sliding mode control strategies were compared with the proposed one. Theoretical stability proofs were addressed for each structure. The controllers were implemented in a real fuel cell power system. Results analysis focused in robustness and chattering, an energy consumption effect.